Against Securitism, the New Breed of Actualism in Consequentialist Thought. Issue 2 (20th August 2015) - VESSEL, JEAN-PAUL
Abstract : In Commonsense Consequentialism: Wherein Morality Meets Rationality, Douglas Portmore introduces a novel position regarding the actualist–possibilist controversies in consequentialist thought – securitism – a position he argues is theoretically superior to the standard views in both the actualist and possibilist camps. After distinguishing the two camps through an examination of the original Procrastinate case, I present Portmore's securitism (a new species of actualism) and its implications regarding his modified Procrastinate case. I level two serious objections against securitism: (i) that it implausibly implies that morality is radically more demanding for the virtuous than it is for the vicious and (ii) that it fails to recognize moral vice in a wide range of cases. I close by arguing that a possibilist variant of Portmore's securitist view is impervious to such objections and thus appears theoretically superior to the actualist version Portmore promotes.